Answer:
P ( x ) = -0.7 (x - 2)²(x + 3)
Step-by-step explanation:
<u>We are given</u> :
P ( x ) , has a root of multiplicity 2 at x = 2
and a root of multiplicity 1 at x = − 3
Then
P ( x ) = a (x - 2)²(x + 3) ; where ‘a’ is a real number.
P ( x ) = a (x - 2)²(x + 3)
= a (x² - 4x + 4)(x + 3)
= a [x³ - 4x² + 4x + 3x² - 12x + 12]
P (0) = -8.4
⇔ a [(0)³ - 4(0)² + 4(0) + 3(0)² - 12(0) + 12] = -8.4
⇔ 12 a = -8.4
⇔ a = (-8,4) ÷ 12
⇔ a = -0,7
<u>Conclusion</u> :
P ( x ) = -0.7 (x - 2)²(x + 3)
Step-by-step explanation:
✓(-1/6×4/7)+(-1/6×-2/5)
✓(-4/42)+(2/30)
✓(-2/21)+(1/15)
✓(-2/21+1/15)
=-<u>1/35</u>
Use trigonometry.
sinQ = 14/50 = 0.28
-> angle Q = sin^-1(0.28) = approx 16 degrees
-> cosQ = A/H -> cos16 = PQ/50
=> PQ = 50*cos16 = approx 48.06
So yea.
I would say she should spin the wheel because, if she rolled the dice it would take a long time to get 2 5's on both dice at one time.
Hope this helps!